2020
DOI: 10.1002/bit.27484
|View full text |Cite
|
Sign up to set email alerts
|

S‐adenosylmethionine and methylthioadenosine boost cellular productivities of antibody forming Chinese hamster ovary cells

Abstract: The improvement of cell specific productivities for the formation of therapeutic proteins is an important step towards intensified production processes. Among others, the induction of the desired production phenotype via proper media additives is a feasible solution provided that said compounds adequately trigger metabolic and regulatory programs inside the cells. In this study, S-(5′-adenosyl)-L-methionine (SAM) and 5′-deoxy-5′-(methylthio)adenosine (MTA) were found to stimulate cell specific productivities u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 48 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…All sampling and measurement procedures were performed with three technical replicates. The determination of cell cycle distribution was performed as described before [21]. All sampling and measurement procedures were performed with two technical replicates.…”
Section: Extracellular and Cell Cycle Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…All sampling and measurement procedures were performed with three technical replicates. The determination of cell cycle distribution was performed as described before [21]. All sampling and measurement procedures were performed with two technical replicates.…”
Section: Extracellular and Cell Cycle Analysismentioning
confidence: 99%
“…Own studies have already revealed that MTA addition diminished growth, increased CSP, altered cell cycle phases and cell size [21]. Consequently, MTA should be considered as a multi-layer regulator of cell growth, cell cycle, and protein formation that is a highly promising additive for boosting CSP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the compartment-specific analytical approach has shown its suitability for multiple metabolomic studies investigating CHO cells under in vivo-like conditions [8,15,[24][25][26][27][28][29][30]. The latter is enabled by fast and standardized metabolism inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms that explain the phenotype remain fragmented. Recently, Verhagen et al (2020a,b) [28,29] demonstrated that cell-cycle arrest could be achieved by exposing CHO cells to the effector 5′-deoxy-5′-(methylthio)adenosine (MTA), which increased CSP by 50%.…”
mentioning
confidence: 99%